CHALLENGES OF ENVIRONMENTAL POLICE ACTIVITY IN THE INSPECTION AND PROTECTION OF THE ENVIRONMENT - Morganti Martins Silva, Daniela; de Giorge Cerqueira, Homero (Revista Gênero e Interdisciplinaridade, 2026)
This scientific article provides an in-depth analysis of the challenges faced by environmental police in the inspection and protection of the environment in Brazil, from constitutional, administrative, and environmental perspectives. It seeks to understand the legal framework of environmental police power, its structuring principles, legal foundations, and the main practical obstacles faced by enforcement agencies. The research employs a deductive, bibliographic, and documentary methodology, grounded in the Federal Constitution of 1988, pertinent infraconstitutional legislation, especially Law No. 6,938/1981, Law No. 9,605/1998, Decree No. 6,514/2008, and Complementary Law No. 140/22011, specialized doctrine, and the jurisprudence of superior courts. The classical attributes of police power, discretion, coercibility, self-enforcement, and imperativeness , are examined, along with their transposition to the environmental domain and the tensions arising therefrom in the context of a federative state of continental dimensions. Structural, technological, normative, federative, and institutional challenges compromising the effectiveness of environmental protection are also analyzed. The conclusion is that strengthening the environmental policy requires investment in human resources and technology, improvement of federative cooperation, technical qualification of agents, and consolidation of an institutional culture of environmental protection grounded in legality and efficiency.